PENGARUH METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 4 SDN PETIR 3 - Khofifah Rizkyah; Candra Puspita Rini; Dayu Retno Puspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of learning outcomes in mathematics among students who are taught using the methodproblem solving with students who are taught using conventional methods. This study used a quasi-experimental research method with a research designnonequivalent control group design. The population subjects in this study were all of class IV at SDN Petir 3, by taking samples of two classes, namely class 4A and 4B which consisted of 30 students from class 4A as the experimental class and 28 students from class 4B as the control class. Data collection techniques using a mathematical test instrument in the form of multiple choices. To test the pretest hypothesis in this study using a testindependent samples test from the t test obtained a significance value of 0.757 > 0.05, it can be concluded that there is no significant difference between the average pretest scores of the control class and the experimental class. Whereas for testing the post-test hypothesis from the results of the t test obtained a significance value of 0.001 <0.05. So it can be concluded that there is a significant difference between the average post-test scores of the control class and the experimental class. This can be interpreted that the results of student learning by using the methodproblem solving higher than using conventional learning methods.